2021
DOI: 10.1021/acssensors.1c01339
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Thermodynamics and Kinetics for the Effects of Relative Humidity on the Electrolyte in Electrochemical Toxic Gas Sensors

Abstract: In this paper, the physical chemistry of the absorption and desorption of water vapor for electrochemical gas sensors with commonly used sulfuric acid as the electrolyte is investigated. Electrochemical gas sensors are being increasingly used for monitoring toxic gases in the environment, and they are, in principle, simple devices, but in practice, their operation is complex. In particular, changes in atmospheric humidity and temperature can have significant effects on the sensor output. A model has been devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Second, most of the studies focused on formaldehyde concentration ranges that were higher than typical indoor (~17 ppb) [31] or ambient (~3 ppb) [32] levels in the United States. In addition, previous studies have reported the influence of temperature and RH on the performance of electrochemical sensors [25,[33][34][35][36]. However, some studies report contradictory results regarding the effect of RH [37], and many studies only report qualitative results [30,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Second, most of the studies focused on formaldehyde concentration ranges that were higher than typical indoor (~17 ppb) [31] or ambient (~3 ppb) [32] levels in the United States. In addition, previous studies have reported the influence of temperature and RH on the performance of electrochemical sensors [25,[33][34][35][36]. However, some studies report contradictory results regarding the effect of RH [37], and many studies only report qualitative results [30,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In general, two-dimensional (2D) materials are recognized as promising sensors with advantages such as high surface area and surface functionality. Ultra-thin materials such as palladium nanosheets (PdNS) and MXene (2D transition metal carbides, nitrides, and carbon nitride family) are trending nanocomposite materials for many types of gas and humidity sensing [ 15 , 16 , 17 ]. However, there are limitations to the mass production of nanomaterials with high surface area as well as uniform quality.…”
Section: Introductionmentioning
confidence: 99%
“…By reducing the humidity, the distance between layers is reduced and the resistance is restored. Thus, the main mechanism in Mxene is the change of layer spacing [ 17 ]. Hence, maintaining the layer-by-layer spacing in Mxene without water intercalation at high humidity levels is a major limitation.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Electrochemical sensors are also commercialized, but they are less sensitive than MOS gas sensors and susceptible to temperature and humidity changes. 20,21 Other types of H 2 S sensors have been proposed, such as colorimetric sensors, 22 surface acoustic wave gas sensors, 23 and sensors made using conductive materials (e.g., graphenes and polymers). 24,25 However, these sensors are hindered by challenges related to selectivity or ppb-level detection.…”
mentioning
confidence: 99%
“…Various types of H 2 S sensors have been proposed and used to address these requirements. , The most common H 2 S sensors are based on semiconducting metal oxides; they have low costs and are operated rapidly and easily. However, metal oxide semiconductor (MOS) gas sensors typically have poor selectivity because they react to all reducing or oxidizing gases. , Electrochemical sensors are also commercialized, but they are less sensitive than MOS gas sensors and susceptible to temperature and humidity changes. , Other types of H 2 S sensors have been proposed, such as colorimetric sensors, surface acoustic wave gas sensors, and sensors made using conductive materials (e.g., graphenes and polymers). , However, these sensors are hindered by challenges related to selectivity or ppb-level detection. Decorating conducting materials, such as MOS, , graphenes, and carbon nanotubes (CNTs), with metal and MOS nanoparticles (NPs) has recently been used to achieve sensor selectivity and ppb-level detection.…”
mentioning
confidence: 99%